Short-Term Psychological Support for Civilians Exposed to the January 2015 Terrorist Attacks in France. Issue 6 (December 2022) - Vuillermoz, Cécile; Prieto, Nathalie; Pirard, Philippe; Baubet, Thierry; Stene, Lise Eilin; Vandentorren, Stéphanie
Abstract: Introduction: Following a terrorist attack, responses to a psychosocial disaster range from low-intensity initiatives to high-intensity treatment. Some studies described post-disaster psychosocial services and planning across Europe. However, little is known about the psychosocial support (PS) actually delivered after terrorist attacks. Study Objective: This study assesses prevalence and the factors associated with not receiving short-term PS among terror-exposed people with probable mental health disorders following the January 2015 terrorist attacks in France. Methods: This study used data from the first wave of a longitudinal survey conducted six months after the attacks. Prevalence and factors associated with not receiving PS were described in the immediate period (48 hours), the early post-immediate period (48 hours-one week), and the medium-term (over one week) using a robust Poisson regression for each of the three periods. Results: Nearly one-half of the participants (N = 189) did not receive PS in any period (46.6% in the immediate period, 45.5% in the early post-immediate period, and 54.5% in the medium-term). In each period, not receiving PS was associated with not being very close to the attack sites. Not receiving PS in the immediate period was also associated with being a direct witness (DW) rather than being directly threatened (DT) and not having support in daily life; in the early post-immediate period, not receiving PS was associated with not having a peri-traumatic dissociation experience and being followed for a psychological problem before the attacks; and in the medium-term period, it was associated with perceived social isolation. Conclusion: The characteristics of the terror exposure and social support seemed to influence presence or absence of PS after the terrorist attack and highlight the need for strategies to reach out to people regardless of the type of exposure.